The Role of Profitability in Mediating the Effect of Managerial Ownership, Dividend Policy, and Investment Policy on Company Value - Fitriah Ulfah (Innovation Business Management and Accounting Journal, 2026)
The objective of this research is to analyze the role of profitability in mediating the influence of managerial ownership, dividend policy, and investment policy on firm value. This study uses secondary data collected from food and beverage companies listed on the Indonesia Stock Exchange for the period 2021-2023. Sampling was conducted using purposive sampling, resulting in a sample of 39 companies. This study employed quantitative research with path analysis techniques. The results show that managerial ownership, dividend policy, and investment policy have a significant effect on profitability, dividend policy has a significant effect on firm value, while managerial ownership and investment policy have no significant effect on firm value. Furthermore, profitability cannot mediate the relationship between managerial ownership, dividend policy, and investment policy on firm value.